2017
DOI: 10.1007/s12031-017-1014-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Expression in Lymphocytes: a Powerful Indicator of Degeneration in Parkinson’s Disease, Amyotrophic Lateral Sclerosis and Ataxia

Abstract: Deregulated neurotrophin is an etiological factor in the pathology of neurodegenerative diseases (ND) that are clinically different entities but characterised by similar limb dysfunction. Earlier validation of peripheral biomarkers can provide significant translational benefit to ND patients. We analysed brain-derived neurotrophic factor (BDNF)-tropomyosin possessing tyrosine-related kinase (Trk B) and its key downstream proteins which are implicated in ND such as Parkinson's disease (PD), amyotrophic lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Expression levels of the below-mentioned 13 mRNAs that are potentially involved in the pathogenesis of ALS, have been compared between ALS and normal control subjects and disease control patients by using quantitative polymerase chain reaction (qPCR) (Table 2) [135,136,137,138].…”
Section: Rnas As Biomarker Candidates Of Sporadic Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of the below-mentioned 13 mRNAs that are potentially involved in the pathogenesis of ALS, have been compared between ALS and normal control subjects and disease control patients by using quantitative polymerase chain reaction (qPCR) (Table 2) [135,136,137,138].…”
Section: Rnas As Biomarker Candidates Of Sporadic Alsmentioning
confidence: 99%
“…Neurotrophic factors, including BDNF, neurotrophic receptor tyrosine kinase 2 (NTRK2), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), AKT serine/threonine kinase 1 (AKT1), glycogen synthase kinase 3β (GSK3β), nuclear factor κB (NFκB), and Fas ligand (FASLG), play roles in the development and synaptic plasticity of the nervous system, suggesting pathogenic roles in neurological diseases [144]. Indeed, studies using qPCR demonstrated an increase of the expression levels of mRNAs of all these neurotrophic factors in peripheral blood leukocytes (PBL) and four of them (BDNF mRNA, PIK3CA mRNA, AKT1 mRNA, and NFκB mRNA) in whole blood from ALS patients [138].…”
Section: Rnas As Biomarker Candidates Of Sporadic Alsmentioning
confidence: 99%
“…It was shown that a low level of BDNF corresponds to numerous lifestyle-related diseases such as MetS [73] and associated disorders like obesity [74], type 2 diabetes [75], heart failure [76], and acute coronary syndrome [77]. Moreover, low levels of BDNF were also related with the development of four main neurodegenerative diseases with selective death of specific neuronal populations [78] such as Parkinson [79], Alzheimer [8082], and Huntington diseases [52] and amyotrophic lateral sclerosis [83] as well as with neuropsychiatric disorders such as dementia [84], depression [85], schizophrenia [86], and bipolar disorder [87], which cause severe personal suffering and disability [57].…”
Section: Introductionmentioning
confidence: 99%
“…However, some mRNAs are differentially expressed in ALS patients and could potentially serve as diagnostic biomarkers. These include kinesins (e.g., KIF5C and KIFC3) and the dynactin subunit DCTN1 which are involved in axonal transport [ 107 , 108 , 109 ], neurotrophic factors (e.g., Trk-B, BDNF, PI3K, AKT, NFκB, GSK3β, and FASL) involved in cell proliferation and differentiation [ 110 ], apoptotic regulatory proteins CyFIP2 and RbBP9 [ 111 ], the vascular endothelial growth factor-A (VEGF-A) and chemokine ligand (CCL2) which are thought to play a role in neuroprotection [ 112 ], and the transcription factor Nurr1 which is involved in neuroinflammation [ 113 ]. However, most of these mRNAs are similarly dysregulated in other neurodegenerative diseases or have not been tested for ALS specificity, with exceptions for FasL mRNA, which showed a significant increase in the peripheral blood leukocytes (PBL) of ALS patients relative to PD, ataxia, and healthy controls [ 114 ], and Nurr1, which was downregulated in the peripheral blood of PD patients [ 114 ] and upregulated in ALS [ 113 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%